Development of an integrated pest management system for vine mealybug, Planococcus ficus (Signoret), in vineyards in the Western Cape Province, South Africa - Walton, Vaughn M. (Vaughn Martin) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2003.